2013
DOI: 10.1126/science.1228806
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine in Floral Nectar Enhances a Pollinator's Memory of Reward

Abstract: Plant defence compounds occur in floral nectar, but their ecological role is not well-understood. We provide the first evidence that plant compounds pharmacologically alter pollinator behaviour by enhancing their memory of reward. Honeybees rewarded with caffeine, which occurs naturally in nectar of Coffea and Citrus species, were three times more likely to remember a learned floral scent than those rewarded with sucrose alone. Caffeine potentiated responses of mushroom body neurons involved in olfactory learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
363
5
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(387 citation statements)
references
References 36 publications
11
363
5
8
Order By: Relevance
“…There are numerous reports of bees poisoned by secondary metabolites in nectar and pollen [6,10], and bees can incur reproductive costs when they consume these compounds [11]. However, limited evidence demonstrates that secondary metabolites can benefit bees, for example by enhancing memory and foraging efficiency [12], reducing parasite infection [13] and controlling pathogenic fungi [14]. The potential therefore exists for plant secondary metabolites to play an important role in mediating tritrophic interactions among plants, pollinators and parasites, but how costs and benefits of chemical consumption affect bee survival and reproduction remains relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports of bees poisoned by secondary metabolites in nectar and pollen [6,10], and bees can incur reproductive costs when they consume these compounds [11]. However, limited evidence demonstrates that secondary metabolites can benefit bees, for example by enhancing memory and foraging efficiency [12], reducing parasite infection [13] and controlling pathogenic fungi [14]. The potential therefore exists for plant secondary metabolites to play an important role in mediating tritrophic interactions among plants, pollinators and parasites, but how costs and benefits of chemical consumption affect bee survival and reproduction remains relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic distribution of caffeine, or xanthine alkaloids more generally, is highly sporadic and usually restricted to only a few species within a given genus (12,13). Caffeine accumulates in various tissues, where it may deter herbivory (14,15) or enhance pollinator memory (16). Numerous studies over the past 30 y have indicated that although several possible routes exist, the same canonical pathway to caffeine biosynthesis has evolved independently in Coffea (coffee) and Camellia (tea) involving three methylation reactions to sequentially convert xanthosine to 7-methylxanthine to theobromine to caffeine ( Fig.…”
mentioning
confidence: 99%
“…When fed with increasing concentration of caffeine, bed bugs consumed significantly less (36%) blood and produced significantly fewer eggs, 64% between the control and the highest concentration (50 ppm) of caffeine in the blood. Wright et al [42] found that honey bees rewarded with naturally occurring caffeine from Coffea and Citrus species, were three times as likely to remember the floral scent as was honey bees rewarded with sucrose alone. It also improves the honey bees' long-term memory for flowers.…”
Section: Discussionmentioning
confidence: 99%